Mental Health Shadows: Accompanying Medication Compliance Towards Healing Tuberculosis Patients - Indra Fajarwati Ibnu; Shanti Riskiyani; Rizky Chaeraty Syam (Journal of Public Health and Pharmacy, 2026)
Introduction: Mental health disturbances may adversely affect treatment adherence and outcomes among pulmonary tuberculosis (TB) patients, but there is a lack of consensus on the relationship. Despite TB being one of the top ten causes of death worldwide, particularly in low and middle-income countries, the comorbidity between TB and mental health disorders has been relatively neglected. Evidence shows that TB and mental health have a bidirectional relationship, so we aimed to elucidate the challenges linked with integrating mental health into TB care with an emphasis on novel suggestions for improving treatment success. Methods: This qualitative study utilized a phenomenological design and was implemented in hospitals and community health centers in Makassar City for six months. We enrolled 10 patients of coexisting pulmonary TB and mental health disturbances. We collected data through participant observations and in-depth semi-structured interviews. Ethics approval was obtained from the Health Research Ethics Commission, Faculty of Public Health Hasanuddin University No.583/UN4. 14. 1/TP. 01.02/2024 and written informed consent was obtained from participants. Result: Mental health disturbances related to poor TB treatment adherence. Both depression and anxiety patients cited disengagement from treatment because of apathy, lack of motivation, and social isolation due to stigma. Inadequately treated mental health symptoms also aggravated physical TB symptom's severity causing further increased non-adherence. Themes of stigma, limited mental health support and positive effects of social networks were identified through statistical analyses. To our surprise, those with the most solid family support fared better despite serious mental illnesses. Conclusion: Collectively, our findings underscore the importance of mental health disturbances on treatment adherence in TB. The findings from this research highlight the critical importance of incorporating mental health screening and psychosocial support into TB programmes. Studies to come should assess the effectiveness of such interventions, paving the way for integrated care of TB patients.